Training in pediatric skin of color: Suggested curricular guidelines of the pediatric dermatology research alliance special interest group in pediatric skin of color. (21st August 2021) - Silverberg, Nanette B.; Jacob, Sharon; Heath, Candrice; Gonzalez, Mercedes; Yu, Jiade; Luu, Minnelly; Benjamin, Latanya; Kenner‐Bell, Brandi; Oboite, Michelle; Castelo‐Soccio, Leslie; Stein, Sarah L.
Abstract: Background: Deficiencies in the skills necessary to diagnose and manage patients with skin of color may contribute to health disparities. The Pediatric Dermatology Research Alliance Special Interest Group in Pediatric Skin of Color (PSOCG) convened to generate a curriculum of topics required for basic pediatric skin of color (PSOC) education for medical students and residents in dermatology to improve the quality of education in PSOC. Methods: A survey was distributed to the PSOCG members to assess expert opinion regarding critical topics for inclusion in a basic PSOC syllabus. Video conference and two rounds of survey were used to rank topics for inclusion and to highlight the underlying need for inclusion. Results: Group members composed of academic pediatric dermatologists with teaching responsibilities including skin of color topics for dermatology residents and medical students. Learning objectives were developed for an educational lecture on basic science, and clinical conditions affecting PSOC were grouped by age—infantile, pediatric, and adolescent skin conditions affecting the PSOC population were identified for inclusion with rank score based on specific parameters including greater frequency in skin of color, nuances in skin of color, and need for medical workup. Conclusions: Increased focus on PSOC education is needed to improve quality of care for children of color through enhanced knowledge. Inflammatory, genetic, and particularly primary pigmentary disorders should be the focus of a broad curriculum in pediatric skin of color education for medical trainees. Objectives should include improved diagnosis, treatment, and ability to educate patients and their families regarding the nature of their conditions.